The Republic of Korea’s first 70 days of responding to the COVID-19 outbreak - Ladner, Debra; Hamaguchi, Katsumasa; Kim, Kyuri (KDI School of Public Policy and Management, Global Delivery Initiative, 2020)
The COVID-19 pandemic has become a daunting global crisis with profound health, economic, and social impacts felt across the world. As of April 9, 2020, more than 1.5 million positive cases had been confirmed and nearly 90,000 people had died as a result of the virus. As the disease continues to spread, governments are tackling this crisis in different ways, and their efforts are yielding varying results, with some countries continuing to experience increasing numbers of new cases daily and others starting to see a flattening of the growth curve. The Republic of Korea was one of the first countries to respond to COVID-19. The first positive case was identified on January 20, 2020, and daily confirmed cases peaked at 813 on February 29. Since then, the number of new cases has declined until reaching about 100 per day in mid-March. Although it remains uncertain how the crisis will play out over the longer term, Korea’s approach has been effective in slowing the spread of COVID-19. Policy makers and practitioners are asking how Korea has been able to achieve this encouraging outcome while many other countries continue to experience exponential growth in their number of new cases. This case study provides an overview of how Korea responded to the outbreak and how it achieved positive results in containing the disease. As was the case in many countries, the basic elements of Korea’s response to COVID-19 combined using diagnostic testing, tracing contacts, isolating confirmed and suspected cases, providing treatment, and encouraging social distancing. Korea’s sense of urgency, strong implementation capacity, and effective communication and public outreach strategy have distinguished the country’s approach and contributed to its effectiveness. Although Korea’s approach may hold lessons for other countries, it is important to note that some elements may not be directly transferable due to contextual factors including differences in information technology infrastructure, data privacy standards, and health care systems. This case study describes how Korea has undertaken prevention efforts, developed testing kits, tested thousands of people, implemented epidemiological investigations, treated patients, and built the institutional capacity needed to respond to this crisis.
Keywords: Health; Nutrition; Population